Time of use pricing for residential customers case of Malaysia - Muzmar, M. A. R. (Institute of Electrical and Electronics Engineers Inc., 2016)
Time-of-Use (TOU) pricing is a rate of prices depending on time period, which having high electricity tariff at peak demand period and lower tariff at off-peak period. In Malaysia, a flat tariff is applied on residential customer disregard the time of use. Simple TOU pricing is applied on industrial and commercial customers where they pay lower tariff for the electricity used during night time and higher tariff for daytime usage. This to encourage the customer to shifts their electricity usage from peak demand period (daytime) into low demand period (night time). The same TOU pricing cannot be implemented to residential customers since their load is already low during daytime but high during night time (8pm-12pm). This paper studies the TOU prices required for residential customers to make a significant impact on peak demand reduction. Practical load profile data from Malaysian residential and commercial customers are used as a case study. The result shows a significant price difference between the peak and off-peak hours are required to ensure the effectiveness of such pricing.